Evaluación del componente huertos familiares y comunitarios del proyecto de vinculación semillas de la esperanza” - Chávez Flores, Luis Antony (2024)
The present research work was conducted in the canton Latacunga in the academic period October - February 2024 with the objective, to evaluate the project of linking seeds of hope in the component of family and community gardens to ensure access to fresh and healthy food for families and communities. For which applying descriptive research using surveys based on indicators as instruments for the collection of information, the results obtained were tabulated in Excel software version 2401 and a map of the participating families and their gardens was georeferenced with the objective, The results obtained were tabulated in Excel software version 2401. In addition, a map of the participating families and their gardens was georeferenced with the objective of elaborating a map of the beneficiaries using the Arc gis online software and builder application, obtaining the following results: the majority of participants are female and their ages range between 38-47 years old and their monthly income is from agriculture, with an average of 5322 for the production of crops and animals.